Analisis Kelayakan e-Rapor Kesehatan Siswa untuk Meningkatkan Peran Orang Tua, Sekolah dan Puskesmas dalam Pemantauan Status Kesehatan Siswa - Retnowati Retnowati; Kemal N Siregar (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2020)
ABSTRACT Background of Study: Student health records are routinely carried out in schools, but only a manual record in the form of a Health Report Book which has many weaknesses for monitoring student health status. Then an electronic student health record (e-Rapor Kesehatan) was developed at the Jagakarsa District Health Center. The aim of this study is to analyze the feasibility to develop an electronic student health record prototype to increase the role of parents, schools and health center in monitoring student health status to be implemented.  Methods: This study provides a complete TELOS  descriptive analysis (Technology Feasi-bility, Economic, Legal, Operational and Schedule Feasibility) of the electronic student health record prototype. Results: Based on the TELOS analysis conducted that Technology Feasibility, Economic, Operational and Schedule Feasibility was appropriate for the development of electronic student health records prototype. However, the legal aspect still needed to be strengthened, because it was not yet supported by the existence of regulations or standard guidelines for the use of electronic student health records. Conclusion: In conclusions, electronic student health records prototype is feasible to be developed. In the future, policy advocacy related to the legal aspects of using electronic student health records needs to be done so that electronic student health records can be implemented. Keywords: Feasibility analysis, student health record, student’s health